Observation of the resonant character of the [zeta] (4430) - state - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; et al. (Physical review letters, 2014)
Resonant structures in B0→ψ′π−K+ decays are analyzed by performing a four-dimensional fit of the decay amplitude, using pp collision data corresponding to 3 fb−1 collected with the LHCb detector. The data cannot be described with K+π− resonances alone, which is confirmed with a model-independent approach. A highly significant Z(4430)−→ψ′π− component is required, thus confirming the existence of this state. The observed evolution of the Z(4430)− amplitude with the ψ′π− mass establishes the resonant nature of this particle. The mass and width measurements are substantially improved. The spin parity is determined unambiguously to be 1+.
Im Titel ist zeta als griechischer Buchstabe dargestellt
Im Titel ist "-" hochgestellt
Gesehen am 24.07.2020